Composite current collector, composite pole piece, lithium battery and preparation method

By providing an adhesion layer formed by crosslinking agent, reinforcement and thermal initiator between the organic matter liner of the composite fluid collecting fluid and the conductive layer, the problem of low adhesion between the composite fluid collecting fluid is solved, and the mechanical properties are significantly improved and Adhesion improves the performance and life of lithium batteries.

CN119447313APending Publication Date: 2025-02-14ADVANCED MATERIALS TECH (BEIJING) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410443324.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-07
Filing Date
2024-04-12
Publication Date
2025-02-14

Smart Images

  • Figure CN119447313A_ABST
    Figure CN119447313A_ABST
Patent Text Reader

Abstract

The invention provides a composite current collector, a composite pole piece, a lithium battery and a preparation method. The composite current collector comprises an organic matter lining plate, the conductive layer is arranged on at least one side of the organic matter lining plate; the adhesive layer is arranged between the organic matter lining plate and the conductive layer and is configured to enhance the adhesive force between the organic matter lining plate and the conductive layer; wherein the adhesion layer is formed by coating at least one surface of the organic matter lining plate with a cross-linked polymer, the cross-linked polymer is at least obtained by carrying out a cross-linking polymerization reaction on a cross-linking agent, a reinforcing agent and a thermal initiator, the cross-linking agent is used for reinforcing the adhesion of the cross-linked polymer in the cross-linking polymerization reaction process, and the reinforcing agent is used for reinforcing the adhesion of the cross-linked polymer in the thermal initiator process. The reinforcing agent comprises at least two kinds of organic reactants, and at least one of the at least two kinds of reactants is used for forming a space net structure in the cross-linking polymerization reaction process so as to enhance the mechanical strength of the organic matter lining plate.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This disclosure claims priority to Chinese Patent Application No. 202310988176.1 filed in China on August 7, 2023, the entire contents of which are incorporated herein by reference. Technical Field

[0004] The present disclosure relates to the field of batteries, and in particular to a composite current collector, a composite pole piece, a lithium battery and a preparation method thereof. Background Art

[0005] The current collector is one of the important components of lithium-ion batteries. Its function is to carry active materials, collect and conduct electrons. An ideal lithium-ion battery current collector should meet the following characteristics: high electrical conductivity, good chemical and electrochemical stability, high mechanical strength, good compatibility and binding force with electrode active materials, low cost and easy availability, and light weight. Traditional current collectors generally use aluminum foil as the positive electrode current collector and copper foil as the negative electrode current collector. However, copper foil and aluminum foil are difficult to meet people's increasingly high performance requirements for lithium-ion battery current collectors. In order to improve the performance of current collectors, people have developed composite current collectors. Compared with traditional metal foils, composite current collectors have the advantages of high conductivity, low cost, and light weight.

[0006] However, the adhesion between the layers of the existing composite current collector is low and unstable, and there is a risk of easy peeling or falling off when encountering external forces, which in turn affects the energy density and performance of the battery. Summary of the invention

[0007] In view of the above technical problems, the present disclosure provides a composite current collector, a composite pole piece, a lithium battery and a preparation method to solve or at least alleviate at least one technical problem existing in the above composite current collector, composite pole piece and lithium battery.

[0008] According to a specific embodiment of the present disclosure, the present disclosure provides a composite current collector, including:

[0009] Organic liner;

[0010] A conductive layer, disposed on at least one side of the organic liner;

[0011] an adhesion layer disposed between the organic liner and the conductive layer and configured to enhance adhesion between the organic liner and the conductive layer;

[0012] The adhesion layer is formed by coating a cross-linked polymer on at least one surface of the organic liner, wherein the cross-linked polymer is obtained by a cross-linking polymerization reaction of at least a cross-linking agent, a reinforcing agent and a thermal initiator, wherein the cross-linking agent is used to enhance the adhesion of the cross-linked polymer during the cross-linking polymerization reaction, and the reinforcing agent includes acrylic acid and dihydroxymethyl dihydroxyethylene urea, wherein the dihydroxymethyl dihydroxyethylene urea is used to form a spatial network structure during the cross-linking polymerization reaction to enhance the mechanical strength of the organic liner.

[0013] In some embodiments, the reinforcing agent accounts for 1%-10% of the cross-linked polymer by weight, wherein the acrylic acid accounts for 0.5%-5% of the cross-linked polymer by weight, and the dimethylol dihydroxyethylene urea accounts for 0.5%-5% of the cross-linked polymer by weight.

[0014] In some embodiments, the crosslinking agent includes at least one of the following: dihydroxymethylurea, monohydroxymethylurea, or a mixture of dihydroxymethylurea and monohydroxymethylurea.

[0015] In some embodiments, the cross-linking agent accounts for 1%-5% of the reinforcing agent by weight.

[0016] In some embodiments, the thermal initiator includes at least one of the following: azobisisobutyronitrile, tert-butyl perbenzoate, and ethyl ethoxypropionate.

[0017] In some embodiments, the thermal initiator accounts for 1%-5% of the cross-linking agent by weight.

[0018] In some embodiments, the thickness of the organic liner is 2-12 μm, and the thickness of the adhesion layer is 0.1-1 μm.

[0019] In some embodiments, the conductive layer includes a conductive main layer and a guiding layer, wherein the guiding layer is located on a side of the conductive main layer close to the adhesion layer, and is used to enhance the adhesion between the conductive main layer and the organic liner.

[0020] In some embodiments, the material of the guiding layer is metal oxide.

[0021] In some embodiments, the composite current collector is a positive composite current collector, the conductive main layer is aluminum, the longitudinal tensile strength MD of the positive composite current collector is ≥ 240 MPa, and the transverse tensile strength TD is ≥ 200 MPa; or,

[0022] The composite current collector is a negative electrode composite current collector, the conductive main layer is copper, and the longitudinal tensile strength MD of the negative electrode composite current collector is ≥220 MPa, and the transverse tensile strength TD is ≥180 MPa.

[0023] In some embodiments, the composite current collector further includes a shielding layer, and the shielding layer is located on a side of the conductive main layer away from the organic liner.

[0024] In some embodiments,

[0025] The conductive layer is symmetrically arranged on both sides of the organic substrate; and

[0026] The shielding layer is symmetrically arranged on two sides of the conductive layer away from the organic liner.

[0027] In some embodiments, the thickness of the conductive layer is 0.11-1.6 μm.

[0028] In some embodiments, the adhesion between the organic liner and the conductive layer is greater than or equal to 5.0 N / 15 mm and less than or equal to 8 N / 15 mm.

[0029] According to a specific embodiment of the present disclosure, the present disclosure provides a composite pole piece, and the composite pole piece includes the composite current collector as described in any one of the above items.

[0030] According to a specific embodiment of the present disclosure, the present disclosure provides a lithium battery, including the composite pole piece as described above.

[0031] According to a specific embodiment of the present disclosure, the present disclosure provides a method for preparing a composite current collector as described in any one of the above items, comprising the following steps:

[0032] Step S1, providing an organic liner;

[0033] Step S2, disposing an adhesion layer on at least one side of the organic liner, configured to enhance the adhesion of the organic liner, comprising:

[0034] Step S21, at least a cross-linking agent, a reinforcing agent and a thermal initiator undergo a cross-linking polymerization reaction to obtain a cross-linked polymer, wherein the cross-linking agent is used to enhance the binding force of the cross-linked polymer during the cross-linking polymerization reaction, and the reinforcing agent includes at least two types of reactants, and at least one of the at least two types of reactants is used to form a spatial network structure during the cross-linking polymerization reaction to enhance the mechanical strength of the organic liner;

[0035] Step S22, coating the cross-linked polymer on at least one surface of the organic liner to form an adhesion layer;

[0036] Step S3, providing a conductive layer on at least one side of the adhesion layer away from the organic liner;

[0037] In some embodiments, the step S1 includes: providing an organic liner, and performing a corona treatment on the organic liner at a power of 2000-3000W.

[0038] In some embodiments, the step S22 includes: coating the cross-linked polymer on at least one surface of the organic liner, and curing the cross-linked polymer at 50° C.-100° C. for 1-10 minutes to form the adhesion layer.

[0039] In some embodiments, step S3 includes:

[0040] Step S31, forming a metal oxide guiding layer on at least one surface of the adhesion layer by an in-situ reaction;

[0041] Step S32 , depositing a metal layer on a surface of the guiding layer away from the adhesion layer by physical vapor deposition, thereby forming a conductive main layer on the surface of the guiding layer.

[0042] In some embodiments, after step S3, the method further includes: forming a shielding layer on a surface of the conductive layer away from the organic liner.

[0043] The embodiments of the present disclosure also provide a method for preparing a composite electrode, including any method for preparing a composite current collector as described above.

[0044] The embodiments of the present disclosure also provide a method for preparing a lithium battery, including any method for preparing a composite electrode as described above.

[0045] Compared with the prior art, the above solution of the embodiment of the present disclosure has at least the following beneficial effects:

[0046] The composite current collector provided by the present disclosure has an adhesion layer arranged between the organic liner and the conductive layer. The adhesion layer is a cross-linked polymer obtained by a cross-linking polymerization reaction of a reinforcing agent, a cross-linking agent and a thermal initiator. The cross-linking agent is used to enhance the adhesion of the cross-linked polymer during the cross-linking polymerization reaction. The reinforcing agent includes at least two types of organic reactants, and at least one of the at least two types of reactants is used to form a spatial network structure during the cross-linking polymerization reaction to enhance the mechanical strength of the organic liner. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] The drawings herein are incorporated into the specification and constitute a part of the specification, showing embodiments consistent with the present disclosure, and together with the specification, are used to explain the principles of the present disclosure. Obviously, the drawings described below are only some embodiments of the present disclosure, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work. In the drawings:

[0048] Figure 1Schematic diagram of the cross-sectional structure of a composite current collector in some embodiments of the present disclosure;

[0049] Figure 2 Schematic diagram of the cross-sectional structure of a composite current collector in some other embodiments of the present disclosure;

[0050] Figure 3 Schematic diagram of the cross-sectional structure of a composite current collector in some other embodiments of the present disclosure;

[0051] Figure 4 Schematic diagram of the cross-sectional structure of a composite current collector in some other embodiments of the present disclosure;

[0052] Figure 5 Schematic diagram of the cross-sectional structure of a composite current collector in some other embodiments of the present disclosure;

[0053] Figure 6 Schematic diagram of the cross-sectional structure of a composite current collector in some other embodiments of the present disclosure;

[0054] Figure 7 Schematic diagram of the process of preparing a composite current collector in some embodiments of the present disclosure;

[0055] Figure 8 Schematic diagram of the process of preparing a composite current collector attachment layer in some embodiments of the present disclosure;

[0056] Fig. 9 Schematic diagram of the process of preparing a composite current collector conductive layer in some embodiments of the present disclosure.

[0057] The reference numerals in the specific implementation manner are as follows:

[0058] Composite current collector 10;

[0059] A polymer composite layer 1, an organic liner 11 and an adhesion layer 12;

[0060] Conductive layer 2, guiding layer 21, conductive main layer 22, shielding layer 23. DETAILED DESCRIPTION

[0061] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0062] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present disclosure belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present disclosure.

[0063] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such product or device. In the absence of more restrictions, the elements defined by the sentence "comprises a" do not exclude the presence of other identical elements in the product or device including the elements.

[0064] In the description of the embodiments of the present invention, the orientations or positional relationships indicated by technical terms such as "upper", "lower", and "thickness" are based on the orientations or positional relationships shown in the accompanying drawings and are only for the convenience of describing the embodiments of the present invention and simplifying the description. They do not indicate or imply that the devices or elements referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, they cannot be understood as limitations on the embodiments of the present invention.

[0065] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0066] In the description of the embodiments of the present invention, the symbol “~” represents the two endpoint data before and after the “~” and all data between the two endpoints. For example, A~B represents all data greater than or equal to A and less than or equal to B.

[0067] Reference to "embodiments" in this disclosure means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the disclosure. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this disclosure may be combined with other embodiments.

[0068] In the related art, composite current collectors have the advantages of high conductivity, low cost and light weight. However, composite current collectors are still facing the following problems: On the one hand, the composite current collector obtained by directly depositing a metal layer on a polymer film by physical vapor deposition has low adhesion between the metal layer and the polymer film, which is only 0.1N / 15mm-0.2N / 15mm, which easily causes the risk of the metal layer peeling off or falling off from the polymer film layer. On the other hand, the surface of the polymer film is easily bombarded by metal particles in the magnetron and evaporation process, which may cause the polymer macromolecules to break and degrade locally, resulting in a significant decrease in the mechanical properties of the polymer film, resulting in weak mechanical properties of the composite current collector and the risk of breaking the band.

[0069] To this end, the present disclosure provides a composite current collector, comprising: an organic liner; a conductive layer, arranged on at least one side of the organic liner; an adhesion layer, arranged between the organic liner and the conductive layer, and configured to enhance the adhesion between the organic liner and the conductive layer; wherein the adhesion layer is formed by coating a cross-linked polymer on at least one surface of the organic liner, the cross-linked polymer being obtained by a cross-linking polymerization reaction of at least a cross-linking agent, a reinforcing agent and a thermal initiator, the cross-linking agent being used to enhance the adhesion of the cross-linked polymer during the cross-linking polymerization reaction, the reinforcing agent comprising at least two types of organic reactants, at least one of the at least two types of reactants being used to form a spatial network structure during the cross-linking polymerization reaction to enhance the mechanical strength of the organic liner.

[0070] Therefore, the composite current collector provided by the present disclosure is provided with an adhesion layer between the organic liner and the conductive layer. The adhesion layer is a cross-linked polymer obtained by a cross-linking polymerization reaction of an enhancer, a cross-linking agent and a thermal initiator. The cross-linking agent is used to enhance the adhesion of the cross-linked polymer during the cross-linking polymerization reaction. The enhancer includes at least two types of organic reactants, and at least one of the at least two types of reactants is used to form a spatial network structure during the cross-linking polymerization reaction to enhance the mechanical strength of the organic liner. Therefore, the adhesion between the conductive layer and the organic liner can be enhanced to be greater than or equal to 5.0N / 15mm and less than or equal to 8N / 15mm. At the same time, the mechanical strength of the composite current collector can be improved. When the composite current collector is a positive composite current collector, the longitudinal tensile strength MD is ≥240MPa and the transverse tensile strength TD is ≥200MPa; or, when the composite current collector is a negative composite current collector, the longitudinal tensile strength MD is ≥220MPa and the transverse tensile strength TD is ≥180MPa.

[0071] The embodiments of the present disclosure are described in detail below with reference to the accompanying drawings.

[0072] See also Figure 1The embodiment of the present disclosure provides a composite current collector 10, comprising a polymer composite layer 1 and a conductive layer 2, wherein the conductive layer 2 is located on both sides of the polymer composite layer 1, and the conductive layer 2 completely covers both sides of the polymer composite layer 1, that is, the conductive layer 2 covers the polymer composite layer 1 in the orthographic projection of the polymer composite layer 1. The polymer composite layer 1 comprises an organic liner 11 and an adhesion layer 12, wherein the adhesion layer 12 is located on both sides of the organic liner 11, and the adhesion layer 12 is located between the organic liner 11 and the conductive layer 2.

[0073] See also Figure 2 The embodiment of the present disclosure provides a composite current collector 10, comprising a polymer composite layer 1 and a conductive layer 2, wherein the conductive layer 2 is located on one side of the polymer composite layer 1, and the conductive layer 2 completely covers one side of the polymer composite layer 1, that is, the conductive layer 2 covers the polymer composite layer 1 in the orthographic projection of the polymer composite layer 1. The polymer composite layer 1 comprises an organic liner 11 and an adhesion layer 12, wherein the adhesion layer 12 is located on both sides of the organic liner 11, and the adhesion layer 12 is located between the organic liner 11 and the conductive layer 2.

[0074] The adhesion layer 12 can enhance the adhesion between the conductive layer and the organic liner to a value greater than or equal to 5.0 N / 15 mm and less than or equal to 8 N / 15 mm. At the same time, the adhesion layer 12 can improve the mechanical strength of the composite current collector. When the composite current collector is a positive composite current collector, the longitudinal tensile strength MD is ≥240 MPa, and the transverse tensile strength TD is ≥200 MPa; or, when the composite current collector is a negative composite current collector, the longitudinal tensile strength MD is ≥220 MPa, and the transverse tensile strength TD is ≥180 MPa. This can solve the technical problem that the polymer film surface is bombarded by metal particles in the magnetron and evaporation process, causing the polymer macromolecules to break locally and degrade, resulting in a significant decrease in the mechanical properties of the polymer film.

[0075] The material of the organic liner 11 is preferably a polymer film. In some embodiments, the material of the organic liner 11 includes but is not limited to polyethylene (PE), polypropylene (PP), biaxially oriented polypropylene (BOPP), polyethylene terephthalate (PET), biaxially oriented polyethylene terephthalate (BOPET), polyethylene terephthalate (PEN), poly(p-phenylene terephthalamide) (PPTA), polyimide (PI), polycarbonate (PC), polyetheretherketone (PEEK), polyoxymethylene (POM), poly(p-phenylene sulfide) (PPS), poly(p-phenylene oxide) (PPO), polyvinyl chloride (PVC), polyamide (PA) or polytetrafluoroethylene (PTFE). More preferably, when the composite current collector 10 is used as a positive electrode current collector, the organic liner 11 is a PET film or a BOPET film; when the composite current collector 10 is used as a negative electrode current collector, the organic liner 11 is a PP film or a BOPP film. Compared with PET film, BOPET film and BOPP film have better tensile strength, heat resistance, transparency and non-degradation properties than PP film, which are beneficial to improving the performance of composite current collectors. PET or BOPET is cheaper than PP or BOPP, and has stronger tensile strength and heat resistance than PP or BOPP, so it is the preferred substrate. PET or BOPET has no degradation effect on the positive electrode material aluminum, so it is the preferred positive electrode material. However, when used as a negative electrode substrate, direct contact between the electrolyte and PET or BOPET will cause PET or BOPET to degrade, so it is usually not suitable to choose PET or BOPET as the negative electrode substrate, and PP or BOPP is preferred as the substrate for copper.

[0076] The adhesion layer 12 is formed by coating a cross-linked polymer, for example, uniformly coating the surface of the PET and / or BOPP film with a micro-gravure coater, and the adhesion layer is formed by coating a cross-linked polymer on at least one surface of the organic liner, and the cross-linked polymer is obtained by a cross-linking polymerization reaction of at least a cross-linking agent, a reinforcing agent and a thermal initiator, and the cross-linking agent is used to enhance the adhesion of the cross-linked polymer during the cross-linking polymerization reaction, and the reinforcing agent includes at least two types of organic reactants, and at least one of the at least two types of reactants is used to form a spatial network structure during the cross-linking polymerization reaction to enhance the mechanical strength of the organic liner. As an example, for the negative electrode substrate, when copper is selected as the conductive material, PET cannot be selected as the substrate because the electrolyte will degrade PET. When PP is selected as the substrate, the binding force between PP and copper is extremely poor. Therefore, the cross-linked polymer generated by the cross-linking agent reaction is used to enhance the binding force between the PP substrate and copper, so that PP can be well used as the negative electrode substrate. At the same time, direct deposition of copper on the surface of the PP substrate will cause local breakage and degradation of the polymer macromolecules, thereby reducing the mechanical strength of the PP substrate. Therefore, a spatial network structure is formed during the cross-linking polymerization reaction by at least one of the two types of reactants of the enhancer to enhance the mechanical strength of the organic liner.

[0077] In some optional embodiments, the reinforcing agent includes acrylic acid or acrylic acid derivatives, and dimethylol dihydroxyethylene urea. Dimethylol dihydroxyethylene urea is used to form a spatial network structure during the cross-linking polymerization reaction, which can improve the tensile properties of the cross-linked polymer to enhance the mechanical strength of the organic liner. Therefore, the cross-linked polymer generated by the reaction of acrylic acid or acrylic acid derivatives, dimethylol dihydroxyethylene urea and dihydroxymethyl urea can improve the mechanical properties of the polymer current collector 10 and improve the adhesion of the organic liner, thereby increasing the service life of the battery.

[0078] It has been verified through experiments that, when the composite current collector formed by the attachment layer 12 is a positive composite current collector, the conductive main layer is aluminum, and the longitudinal tensile strength MD of the positive composite current collector is ≥240MPa, and the transverse tensile strength TD is ≥200MPa; or, when the composite current collector formed is a negative composite current collector, the conductive main layer is copper, and the longitudinal tensile strength MD of the negative composite current collector is ≥220MPa, and the transverse tensile strength TD is ≥180MPa. Compared with the composite current collector without an attachment layer, the mechanical tensile performance is greatly improved.

[0079] At least two reactants in the reinforcing agent are capable of undergoing polymerization reaction. The weight percentage of the reinforcing agent in the cross-linked polymer is preferably, but not limited to, 1%-10%, such as 2%, 5%, etc.

[0080] The adhesion layer 12 can also reduce the damage to the organic liner 11 during the sputtering of the conductive layer 2 during the preparation of the composite current collector 10. In addition, the cross-linked polymer of the adhesion layer 12 has good thermal stability, which can increase the glass transition temperature of the organic liner 11, thereby improving the thermal stability of the organic liner; and the cross-linked polymer of the adhesion layer 12 has good adhesion to the organic liner, which can increase the bonding force between the organic liner 11 and the conductive layer 2, and prevent the conductive layer 2 from falling off the organic liner 11 during use, thereby improving the conductivity and safety of the battery.

[0081] Preferably, the mass percentage of acrylic acid or acrylic acid derivatives in the cross-linked polymer is 0.5%-5%; the mass percentage of isocyanate or isocyanate derivatives in the cross-linked polymer is 0.5%-5%.

[0082] Acrylic derivatives include, but are not limited to, at least one of acrylate, methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, propyl acrylate, propyl methacrylate, isopropyl acrylate, isopropyl methacrylate, butyl acrylate, butyl methacrylate, isobutyl acrylate, isobutyl methacrylate, tert-butyl acrylate, tert-butyl methacrylate, hexyl acrylate, hexyl methacrylate, isooctyl acrylate, isooctyl methacrylate, glycidyl acrylate, and glycidyl methacrylate.

[0083] The cross-linking agent causes acrylic acid or acrylic acid derivatives to undergo cross-linking polymerization with dihydroxymethyl dihydroxyethylene urea to obtain a cross-linked polymer, thereby improving the bonding force of the adhesion layer 12 and increasing the bonding force between the organic liner 11 and the conductive layer 2. The cross-linking agent includes but is not limited to dihydroxymethylurea, monohydroxymethylurea, or a mixture of dihydroxymethylurea and monohydroxymethylurea, wherein the ratio of dihydroxymethylurea to monohydroxymethylurea in the mixture of dihydroxymethylurea and monohydroxymethylurea is 1:1. The mass percentage of the cross-linking agent to the reinforcing agent is preferably, but not limited to, 1%-5%.

[0084] Thermal initiators include, but are not limited to, azobisisobutyronitrile, tert-butyl perbenzoate, ethyl ethoxypropionate, etc. Preferably, the mass percentage of the thermal initiator to the mass percentage of the crosslinking agent is 1%-5%.

[0085] In some preferred embodiments, the thickness of the polymer composite layer 1 is 2.1-13 μm, wherein the thickness of the organic liner 11 is 2-12 μm, and the thickness of the adhesion layer 12 is 0.1-1 μm. The thickness of the adhesion layer 12 is relatively small, and the increase in the overall thickness of the composite current collector relative to the thickness of the organic liner 11 is negligible. While increasing the bonding force between the organic liner 11 and the conductive layer 2, the thermal stability of the organic liner 11, and the mechanical properties of the composite current collector, the increase in the thickness and weight of the composite current collector 10 is basically negligible. The thickness of the polymer composite layer 1 is micrometer-level, thereby reducing the thickness and weight of the composite current collector 10.

[0086] In some embodiments, the conductive layer may be a single conductive layer 2, such as Figure 1 and Figure 2 As described in the embodiment shown, at this time, the material of the conductive layer 2 can be a metal or an alloy. Metals include but are not limited to aluminum, copper, nickel, titanium, silver, etc., and alloys include nickel-copper alloys, aluminum-zirconium alloys, etc. In some embodiments, the composite current collector 10 is used as a positive electrode current collector, and the conductive layer 2 is metal aluminum. The composite current collector 10 is used as a negative electrode current collector, and the conductive layer 2 is metal copper. The conductive layer 2 is formed by directly depositing a metal layer on a polymer film by physical vapor deposition. The film layer is relatively thin, for example, the thickness of the conductive layer 2 is 0.12 to 3 μm, and the optional thickness is 0.12 to 1 μm. The thinner metal conductive layer reduces the thickness and weight of the composite current collector as a whole.

[0087] In some embodiments, the conductive layer may be a composite conductive layer 2, such as Figure 3 and Figure 4 As shown, the conductive layer 2 includes a guide layer 21 and a conductive main layer 22, wherein the conductive main layer 22 is substantially equivalent to the single conductive layer described in the above embodiment, and the conductive main layer 22 material can be a metal or an alloy. Metals include but are not limited to aluminum, copper, nickel, titanium, silver, etc., and alloys include nickel-copper alloys, aluminum-zirconium alloys, etc. In some embodiments, the composite current collector 10 is used as a positive electrode current collector, and the conductive main layer 22 is metal aluminum; the composite current collector 10 is used as a negative electrode current collector, and the conductive main layer 22 is metal copper.

[0088] like Figure 3 or Figure 4 As shown, the guide layer 21 is disposed between the conductive main layer 22 and the adhesion layer 12. Since the metal conductive layer is directly deposited or sputtered on the adhesion layer 12, it may still not have sufficient adhesion. In order to further enhance the bonding force between the metal conductive layer and the adhesion layer 12, the guide layer 21 can be disposed. The material of the guide layer 21 includes but is not limited to metal oxides. The metal oxide is preferably but not limited to AlO xThe transition of metal oxide can effectively improve the adhesion between the metal conductive layer and the organic substrate 11. In some embodiments, the guide layer 21 includes a metal oxide layer, and the metal oxide layer is formed on at least one surface of the adhesion layer 12 by an in-situ reaction. The metal oxide layer serves as a guide layer between the metal conductive material 22 and the adhesion layer 12, thereby enhancing the bonding force between the conductive main layer 22 and the adhesion layer 12.

[0089] It can be understood that the guide layer 21 is an optional layer structure, see Figure 5 In some embodiments, the conductive layer 2 does not include the guiding layer 21 , and the conductive main layer 22 is directly disposed on the surface of the adhesion layer 12 away from the organic substrate 11 .

[0090] See also Figure 6 In some optional embodiments, the conductive main layer 22 further includes a shielding layer 23 on the side away from the adhesion layer 12. The shielding layer 23 can prevent the conductive main layer 22 from being oxidized, corroded or damaged. The shielding layer 23 can be arranged on the outermost layer of the conductive layer 2 and can be applied to Figure 1-Figure 5 Any embodiment will not be described in detail here, please refer to Figure 6 The embodiments shown are sufficient for understanding.

[0091] Optionally, the thickness of the guide layer 21 is 0.01-0.1 μm, the thickness of the conductive main layer 22 is 0.1-1.5 μm, and the thickness of the shielding layer 23 is 0.01-1.4 μm. The thickness of the conductive layer 2 disclosed in the present invention is much smaller than the thickness of the traditional copper foil or aluminum foil current collector, thereby reducing the weight of the current collector and the battery and increasing the energy density of the battery.

[0092] The bonding force between the polymer composite layer 1 and the conductive layer 2 in the composite current collector 10 can reach 10N / 15mm. In some embodiments, the bonding force between the polymer composite layer 1 and the conductive layer 2 in the composite current collector 10 is greater than or equal to 3.0N / 15mm and less than or equal to 10N / 15mm, which is much greater than the bonding force between the organic liner and the conductive layer in the existing composite current collector.

[0093] According to the specific implementation of the present disclosure, Figure 7 As shown, the present disclosure provides a method for preparing a composite current collector as described in any one of the above items, comprising the following steps:

[0094] Step S1, providing an organic liner;

[0095] Step S2, disposing an adhesion layer on at least one side of the organic liner, configured to enhance the adhesion of the organic liner, includes the following sub-steps, see Figure 8 As shown:

[0096] Step S21, at least a cross-linking agent, a reinforcing agent and a thermal initiator undergo a cross-linking polymerization reaction to obtain a cross-linked polymer, wherein the cross-linking agent is used to enhance the binding force of the cross-linked polymer during the cross-linking polymerization reaction, and the reinforcing agent includes at least two types of reactants, and at least one of the at least two types of reactants is used to form a spatial network structure during the cross-linking polymerization reaction to enhance the mechanical strength of the organic liner;

[0097] In some embodiments, step S21 includes: adding a reinforcing agent, a cross-linking agent and a thermal initiator to a solvent, stirring under closed conditions, and obtaining a modified cross-linked polymer. The solvent can be selected according to actual needs to ensure that the cross-linking polymerization reaction can proceed. Preferably, the solvent is at least one of water or ethanol. The stirring method can be selected according to actual conditions. For example: ultrasonic stirring, electric stirring, mechanical stirring, etc. Preferably, ultrasonic stirring combined with mechanical stirring is used under closed conditions to uniformly mix acrylic acid or acrylic acid derivatives, isocyanates or isocyanate derivatives, cross-linking agents and initiators in the solvent.

[0098] Step S22, coating the cross-linked polymer on at least one surface of the organic liner to form an adhesion layer; preferably, but not limited to, using a micro gravure coater to uniformly coat the cross-linked polymer on at least one surface of the organic liner 11.

[0099] Step S3, providing a conductive layer on at least one side of the adhesion layer away from the organic liner.

[0100] In some embodiments, the step S1 includes: providing an organic liner, and performing a corona treatment on the organic liner at a power of 2000-3000W.

[0101] In some embodiments, the step S22 includes: coating the cross-linked polymer on at least one surface of the organic liner, and curing the cross-linked polymer at 50° C.-100° C. for 1-10 minutes to form the adhesion layer.

[0102] The reaction curing time can be adjusted according to actual conditions. In some optional embodiments, thermal curing can be performed by segmented gradient lighting, for example, curing at 50°C-60°C for 5 minutes, curing at 60°C-80°C for 2 minutes, and curing at 90°C-100°C for 3 minutes.

[0103] In some embodiments, step S3 includes the following sub-steps: Fig. 9 As shown:

[0104] Step S31, forming a metal oxide guiding layer on at least one surface of the adhesion layer by an in-situ reaction;

[0105] Step S32 , depositing a metal layer on a surface of the guiding layer away from the adhesion layer by physical vapor deposition, thereby forming a conductive main layer on the surface of the guiding layer.

[0106] In step S3, a physical vapor deposition method (PVD) is used to form a conductive main layer 22 on the surface of the adhesion layer 12 or the guide layer 21 away from the organic liner 11. More preferably, the conductive main layer 22 is formed on the surface of the adhesion layer 12 or the guide layer 21 away from the organic liner 11 by evaporating metal. The evaporation method is preferably, but not limited to, resist evaporation, electron gun evaporation, etc.

[0107] In some embodiments, after step S3, the method further includes: forming a shielding layer on a surface of the conductive layer away from the organic liner.

[0108] According to some embodiments of the present disclosure, the present disclosure further provides a composite pole piece, comprising the composite current collector 10 provided by any of the above schemes or the composite current collector 10 obtained by the preparation method of the composite current collector provided by any of the schemes.

[0109] According to some embodiments of the present disclosure, the present disclosure further provides a lithium battery, comprising the composite pole piece provided by any of the above schemes.

[0110] According to some embodiments of the present disclosure, the present disclosure further provides a method for preparing a composite pole piece, including the method for preparing a composite current collector provided by any of the above schemes.

[0111] According to some embodiments of the present disclosure, the present disclosure also provides a method for preparing a lithium battery, including a method for manufacturing a composite pole piece provided by any of the above schemes.

[0112] The composite current collector 10 and its preparation process and test data are introduced below through specific embodiments:

[0113] Embodiment 1:

[0114] In this embodiment, the organic liner 11 is a 6 μm thick PET film, and the adhesion layer 12 is located on the upper and lower surfaces of the PET film. The adhesion layer 12 includes a cross-linked polymer formed by the reaction of acrylic acid, dihydroxymethyl dihydroxyethylene urea, dihydroxymethyl urea, and azobisisobutyronitrile in anhydrous ethanol. The thickness of the adhesion layer 12 is 0.5 μm. The guide layer 21 is a metal oxide AlO x The conductive main layer 22 is made of metal Al and has a thickness of 1.0 μm.

[0115] In this embodiment, the preparation method of the composite current collector specifically includes:

[0116] Step S1, performing corona treatment on the PET film under 3000W; adding 5g of acrylic acid, 5g of dihydroxymethyl dihydroxyethylene urea, 0.5g of dihydroxymethyl urea and 0.05g of azobisisobutyronitrile to anhydrous ethanol, performing ultrasonic and mechanical stirring under closed conditions, and stirring at 30°C for 1h to obtain a cross-linked polymer; using a micro-gravure coater to evenly coat the cross-linked polymer on the upper surface and the lower surface of the PET film, and then reacting and curing at 80°C for 8min to form an adhesion layer on the upper surface and the lower surface of the PET film; and

[0117] AlO was sputtered on the adhesion layer on both the upper and lower surfaces of the PET film. x , forming a guiding layer; and vapor-depositing Al on the guiding layer to obtain a composite current collector.

[0118] Embodiment 2:

[0119] The present embodiment 2 is substantially the same as the embodiment 1, and the only difference is that the substrate 11 is a PET film with a thickness of 4.5 μm, and the conductive material layer 22 is metallic copper.

[0120] Embodiment 3:

[0121] The present embodiment 3 is substantially the same as the embodiment 1, and the only difference is that the substrate 11 is a 4.5 μm thick BOPP film, and the conductive material layer 22 is metallic copper.

[0122] Comparative Example 1:

[0123] This comparative example is basically the same as Example 1, and the only difference is that the conductive layer of this comparative example is directly evaporated on the surface of the organic liner, and there is no adhesion layer between the organic liner and the conductive layer.

[0124] Comparative Example 2:

[0125] Comparative Example 2 is substantially the same as Example 2, with the only difference being that the conductive layer of this comparative example is directly evaporated on the surface of the substrate, and there is no modified layer between the substrate and the conductive layer.

[0126] Comparative Example 3:

[0127] Comparative Example 3 is substantially the same as Example 3, with the only difference being that the conductive layer of this comparative example is directly evaporated on the surface of the substrate, and there is no modified layer between the substrate and the conductive layer.

[0128] Table 1 Comparison of composite current collector performance

[0129]

[0130]

[0131] The tensile strength of the composite current collector in Example 1 is 260MPa in the longitudinal MD and 230MPa in the transverse TD. The tensile strength of the composite current collector in Comparative Example 1 is 220MPa in the longitudinal MD and 190MPa in the transverse TD. This indicates that the adhesion layer in the composite current collector disclosed in the present invention greatly improves the tensile strength of the composite current collector. The strength of the modified substrate in Example 1 is also significantly greater than the strength of the substrate in Comparative Example 1, indicating that the modified layer in the composite current collector disclosed in the present invention greatly improves the tensile strength of the composite current collector substrate. The bonding force between the polymer composite layer and the conductive layer in the composite current collector in Example 1 is 8.26N / 15mm. The bonding force between the polymer composite layer and the conductive layer in Comparative Example 1 is 2.33N / 15mm. This indicates that the adhesion layer in the composite current collector in the embodiment of the present invention greatly improves the bonding force between the polymer composite layer and the conductive layer.

[0132] Table 2 Comparison of composite current collector core performance

[0133]

[0134] It can be seen from the performance comparison results of the composite current collector battery cells in Table 2 that the initial discharge capacity of Examples 1-3 of the present application is greater than the initial discharge capacity of the corresponding Comparative Examples 1-3, indicating that the composite current collector battery cells formed in each embodiment of the present application have good discharge performance.

[0135] The initial charge and discharge efficiency of Examples 1-3 of the present application is greater than that of Comparative Examples 1-3, indicating that the composite current collector battery cells formed in the embodiments of the present application have good discharge performance.

[0136] The number of cycles of the capacity retention rate of Examples 1-3 of the present application is greater than the number of cycles of the capacity retention rate of Comparative Examples 1-3, indicating that the composite current collector battery cells formed in the embodiments of the present application have good discharge performance.

[0137] The energy density of Examples 1-3 of the present application is greater than the energy density of Comparative Examples 1-3, indicating that the composite current collector battery cells formed in the embodiments of the present application have good safety performance.

[0138] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present disclosure, rather than to limit them; although the present disclosure has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present disclosure, and they should all be included in the scope of the claims and specification of the present disclosure. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present disclosure is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A composite current collector, characterized in that: include: Organic lining board; A conductive layer, disposed on at least one side of the organic liner; an adhesion layer disposed between the organic liner and the conductive layer and configured to enhance adhesion between the organic liner and the conductive layer; The adhesion layer is formed by coating a cross-linked polymer on at least one surface of the organic liner, wherein the cross-linked polymer is obtained by a cross-linking polymerization reaction of at least a cross-linking agent, a reinforcing agent and a thermal initiator, wherein the cross-linking agent is used to enhance the adhesion of the cross-linked polymer during the cross-linking polymerization reaction, and the reinforcing agent includes acrylic acid and dihydroxymethyl dihydroxyethylene urea, wherein the dihydroxymethyl dihydroxyethylene urea is used to form a spatial network structure during the cross-linking polymerization reaction to enhance the mechanical strength of the organic liner.

2. The composite current collector according to claim 1, characterized in that: The reinforcing agent accounts for 1%-10% of the cross-linked polymer by mass, wherein the acrylic acid accounts for 0.5%-5% of the cross-linked polymer by mass, and the dimethylol dihydroxyethylene urea accounts for 0.5%-5% of the cross-linked polymer by mass.

3. The composite current collector according to claim 1, characterized in that: The crosslinking agent comprises at least one of the following: dihydroxymethylurea, monohydroxymethylurea or a mixture of dihydroxymethylurea and monohydroxymethylurea.

4. The composite current collector according to claim 1, characterized in that: The cross-linking agent accounts for 1%-5% of the reinforcing agent by mass.

5. A composite pole piece, characterized in that: The composite pole piece comprises the composite current collector according to any one of claims 1 to 14.

6. A lithium battery, characterized in that: Including the composite pole piece as described in claim 5.

7. A method for preparing the composite current collector according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step S1, providing an organic liner; Step S2, disposing an adhesion layer on at least one side of the organic liner, configured to enhance the adhesion of the organic liner, comprising: Step S21, at least a cross-linking agent, a reinforcing agent and a thermal initiator undergo a cross-linking polymerization reaction to obtain a cross-linked polymer, wherein the cross-linking agent is used to enhance the binding force of the cross-linked polymer during the cross-linking polymerization reaction, and the reinforcing agent includes at least two types of reactants, and at least one of the at least two types of reactants is used to form a spatial network structure during the cross-linking polymerization reaction to enhance the mechanical strength of the organic liner; Step S22, coating the cross-linked polymer on at least one surface of the organic liner to form an adhesion layer; Step S3, providing a conductive layer on at least one side of the adhesion layer away from the organic liner.

8. A method for preparing a composite electrode, characterized in that: A method for preparing the composite current collector according to claim 7.

9. A method for preparing a lithium battery, characterized in that: Including the method for preparing the composite pole piece as described in claim 8.